Filozoficzne i teologiczne podstawy argumentacji na rzecz edukacji kobiet w Occasional Thoughts Damaris Masham - Usakiewicz, Joanna (Humaniora. Czasopismo Internetowe, 2019)
In 1705, the book titled Occasional Thoughts in Reference to a Vertuous or Christian Life was edited. Damaris Masham (1659–1708), the author of this writing, the daughter of Ralph Cudworth and the friend of John Locke presents in the work her view on women’s education. This article examines the elements of rational reflection upon the world and the concept of a human being, which has led Masham to a radical for her contemporaries conclusion that the proper women’s education should be necessary. Masham’s arguments refer to the equality of people as rational creatures of God, their desire for salvation, defence of faith, and conveying religious teachings, but also they appeal to the significance of women’s social roles as a wife and a mother.